Influencer Marketing Effectiveness and Participant Satisfaction In Paid Webinars: A Case Study of JIH Academy. - Zarita, Kalam Suryatmojo Dim; Muslichah, Istyakara; Suryanugraha, Dim Zarita (Utan Kayu Publishing, 2026)
This study examines the effectiveness of influencer speakers in paid healthcare webinars by comparing participant perceptions and purchase decisions between webinars featuring influencers and non-influencers at JIH Academy. Using a quantitative survey method, data were collected from 135 webinar participants and analyzed descriptively. The study integrates influencer marketing constructs (attractiveness, expertise, originality, homophily, interaction, and image satisfaction) with training evaluation dimensions (perceived trainer performance, perceived usefulness, and perceived efficiency). The findings indicate that webinars led by influencer speakers are perceived slightly more positively across most variables, particularly in interaction, image satisfaction, and purchase decision. Although the differences between influencer and non-influencer webinars are relatively small, influencer speakers demonstrate a consistent advantage in enhancing participant interest and intention to attend future paid webinars. These results suggest that influencer-based promotion can modestly strengthen both marketing effectiveness and perceived webinar quality in healthcare training services.